Logistic Strategy and Organizational Structure in Brazilian Small and Medium-sized Enterprises (Smes) - Xavier, Wescley Silva; Martins, Ricardo S. (Organizations and Markets in Emerging Economies, 2011)
This study evaluates the logistic strategies developed in Small and Medium-sized Enterprises (SMEs) as a response to their organizational structures and planning processes. A multiple case study was carried out in the second largest furniture cluster in Brazil. Based on theoretical models, it was found that the characteristics of a company’s organizational structure had an impact on planning. In the case of companies with a low level of family participation, this impact was intentional, whereas in the case of companies with strongly centralized owner control over decision-making, the impact was unplanned. However, the formal nature of planning does not guarantee that logistics will have strategic aims and, in all cases, it has a strictly reactive nature.
Keywords: logistic strategies; small and medium-sized enterprises; furniture industry; Brazil